2012
DOI: 10.1148/radiol.12110990
|View full text |Cite
|
Sign up to set email alerts
|

Lung Morphology Assessment with Balanced Steady-State Free Precession MR Imaging Compared with CT

Abstract: This study shows bSSFP MR imaging is inferior to CT in imaging parenchymal lung disease; however, this study does demonstrate for the first time a potential role for the bSSFP sequence as an alternative radiation-free noncontrast imaging modality for use in patients with pulmonary fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…Second, we confirmed that trapped air could not be reliably visualised with MRI, as previously demonstrated by Failo et al and more recently by Rajaram et al [14,15]. Trapped air is an early change associated with small airways disease [3,23].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Second, we confirmed that trapped air could not be reliably visualised with MRI, as previously demonstrated by Failo et al and more recently by Rajaram et al [14,15]. Trapped air is an early change associated with small airways disease [3,23].…”
Section: Discussionsupporting
confidence: 83%
“…Magnetic resonance imaging (MRI), as a radiation-free technique, has been introduced as an alternative to CT [11,12]. To date, MRI has been directly compared to CT in only a few studies, using various MRI sequences [13][14][15], but none of those included motion correction free-breathing sequences, such as PROPELLER. The PROPELLER sequence has been designed to be relatively insensitive to respiratory movements, as it enables correction of in-plane motion, rotation and translation [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It would be interesting to apply this approach to the lungs using our technique. A further application is the potential ability to assist in differentiating fibrosis from mimickers such as emphysema (1,6). We know this can be challenging even for expert readers (1,6).…”
Section: Discussionmentioning
confidence: 99%
“…A further application is the potential ability to assist in differentiating fibrosis from mimickers such as emphysema (1,6). We know this can be challenging even for expert readers (1,6). This might be of particular value in patients with combined pulmonary emphysema-fibrosis syndrome, to evaluate the percentage of abnormal lung that is fibrotic (28).…”
Section: Discussionmentioning
confidence: 99%
“…The quality of proton structural MRI of the lungs has improved in recent years through the use of MR sequences such as ultra-short echo time (Lederlin and CrĂ©millieux, 2013) and balanced steady state free precession (Rajaram et al, 2012) to the point where the scans have diagnostic utility in certain conditions.…”
Section: Introductionmentioning
confidence: 99%